Synthesis of Silver Nanoparticles for Antibacterial Activity against Staphylococcus Aureus and Escherichia Coli - Padole, Nitin Nilkanth (Asian Journal of Pharmaceutical Research and Development, 2022)
In Recent year's medication obstruction is a quickly developing issue over the whole world in the treatment of infectious diseases. The widespread use of broad-spectrum antibiotics produced antibiotic resistance for many human bacterial pathogens. Anyway right now, nanotechnology research has been engaging more in restorative businesses with various advantages because of the way that surface area to volume proportion of Nanoparticles is quite large. In this exploration work, Silver Nanoparticles (AgNPs) are prepared by using a reducing agent like sodium borohydride and capping agent polyvinylpyrolidine. The AgNPs were set up by the chemical reduction method. Nanotechnology has its own importance it eventually reduce dose and also have a superior bioavailability than larger particles. The prepared AgNPs were subjected to characterization like particle size, X-Ray diffraction. In addition, the AgNPs drawing much interest in account of their powerful antibacterial movement. The antibacterial activity of AgNPs checked against the bacterial culture of Staphylococcus Aureus and E, coli. The zone of inhibition AgNPs was checked against both microorganisms. The results of this study demonstrate antibacterial activity of AgNPs against the bacterial culture of Staphylococcus Aureus and E, coli.